2008
DOI: 10.1291/hypres.31.1895
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C Is Related to Pulse Wave Velocity Even in Subjects with Normal Serum Creatinine

Abstract: We hypothesized that serum cystatin C can be a more predictable marker of arterial stiffness than serum creatinine and creatinine-based glomerular filtration rate (GFR). The aim of this study is to evaluate whether serum cystatin C is related to arterial stiffness independently of serum creatinine in subjects for whom serum creatinine is normal. A total of 2,018 individuals (1,120 males, 898 females) were enrolled. Mean brachial-ankle pulse wave velocity (baPWV) was used as a marker of arterial stiffness and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…In addition, both pulse pressure and increased aortic pulse wave velocity, manifestations of large vessel stiffness, are independent risk factors for adverse outcomes in this population [6,7]. Furthermore, our group previously reported that serum cystatin C was related to pulse wave velocity in subjects with normal serum creatinine [8,9]. Thus, we thought that serum cystatin C may be related to cardiovascular events irrespective of serum creatinine.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, both pulse pressure and increased aortic pulse wave velocity, manifestations of large vessel stiffness, are independent risk factors for adverse outcomes in this population [6,7]. Furthermore, our group previously reported that serum cystatin C was related to pulse wave velocity in subjects with normal serum creatinine [8,9]. Thus, we thought that serum cystatin C may be related to cardiovascular events irrespective of serum creatinine.…”
Section: Introductionmentioning
confidence: 77%
“…Anti-atherosclerotic activity of cystatin C was identified in an animal model study that showed cystatin C-deficient mice had larger subvalvular plaques compared with control mice [38,39]. Previously, our group reported that cystatin C was related to pulse wave velocity, a marker representing arterial stiffness, independently of serum creatinine and creatinine-based GFR [8]. Increased arterial stiffness is one of the pathological states of vascular damage and is closely associated with atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other cardiovascular risk factors, such as renal dysfunction, as assessed by the serum creatinine or cystatin C levels and pulmonary dysfunction are also reported to be associated with an increase of the brachial-ankle PWV [37][38][39][40] . Increased brachial-ankle PWV values have also been reported in subjects with osteoporosis or sarcopenia [40][41][42] .…”
Section: Other Risk Factors For Cardiovascular Diseasementioning
confidence: 99%
“…[122][123][124][125] Recent studies have suggested that serum cystatin C can reflect artery stiffness. 126,127 Interestingly, data from a population-based study showed that high serum cystatin C levels were associated with increased left ventricular mass, concentric ventricular hypertrophy, and function. 128 However, only recently has research been conducted to evaluate whether circulating cathepsin levels can be used as a predictive biomarker for patients with CCVD.…”
Section: Circulating Cathepsins and Cystatin C As Biomarkers For Ccvdmentioning
confidence: 99%